Thumb-pads up—a new species of thick-thumbed bat from Sumatra (Chiroptera: Vespertilionidae: Glischropus) - Csorba, Gábor; Görföl, Tamás; Wiantoro, Sigit; Kingston, Tigga; Bates, Paul J. J.; Huang, Joe Chun-Chia (Zootaxa, 2015)
To date, three species of the genus Glischropus are recognized from the Indomalayan zoogeographic region—G. bucephalus from the Indochinese subregion, G. tylopus from the Sundaic subregion (Peninsular Thailand and Malaysia, Borneo, Sumatra, Moluccas) and G. javanus, restricted to Java. The investigation of the holotype and three topotype specimens of G. batjanus supported the view that the name was previously correctly regarded as the junior subjective synonym of G. tylopus. During review of material recently collected in southwestern Sumatra, Indonesia, one specimen of a yet undescribed species of Thick-thumbed bat was identified. G. aquilus n. sp. markedly differs from its congeners by its dark brown pelage, nearly black ear and tragus, and in skull proportions. The phylogenetic analysis based on cytb sequences also supports the specific distinctness of G. aquilus n. sp. Its discovery brings the count to 88 species of bats known from Sumatra.